What are the main factors affecting gender pay inequality at banking sector of Azerbaijan? A study on the main causes of gender pay inequality among bank employees in Azerbaijan - Azadi, Firangiz (ADA University, 2020)
The purpose of this research is to examine the causes of the gender pay inequality among bank employees in Azerbaijan. It is aimed to measure the gender pay gap among male and female employees working in banking industry and discover the main causes of this observed gap. The importance of this study is that by conducting detailed examination can increase the awareness of people toward this problem and can positively affect the empowerment of women in the future. Although positive changes have been experiencing related to the women empowerment, the problem of gender wage gap still exist. Gender wage gap is considered as a difference in average income of male and female employees. In academic literature, the gender pay inequality is explained by various differences in individual characteristics of male and female employees or difference in job conditions and job characteristics. Human capital theories refer to the personal differences, skills, and competencies of males and females while explaining the gender pay gap. There are also other explanations of this gap considering job characteristics in the workplace. In this research, the effects of six independent variables including educational level, work experience, self-development, career breaks, working in the management, and self-selection criteria, gender wage gap has been tested. Consequently, a quantitative research method has been used in order to explore the possible causes of the gender wage gap in banks operating in Azerbaijan. This quantitative research method has involved a method of conducting surveys among male and female employees working in various banks of Azerbaijan. Consequently, the data gathered from 253 participants has been analyzed. Thus, three analytical tools – descriptive analysis, Difference in Difference estimation, and Oaxaca – Blinder decomposition methods have been applied using STATA – analytical software. Overall, 6 hypotheses has been tested by using these above-mentioned analytical tools. Firstly, it has been found that in our sample data, number of male employees that are high educated is more than the number of female employees. It has been observed that educational level of employees has the particular effect on the gender pay gap between males and females. Our first hypothesis that educational level of the employees is negatively related with the gender pay inequality, is proved since male employees have higher educational level than female employees, the gap in monthly income between these two groups exists. Secondly, it has been observed that male employees have longer career or work experience than female employees. It has been discovered that work experience is negatively related with the gender wage gap and our second hypotheses has claimed this argument as well. When the female workers are more experienced, they get higher level of income, and therefore the wage gap can be reduced. Consequently, since in our sample data, male employees have more work experience and females have less work experience, a gap in their income exists. It can be related to the fact that females usually have more family of child responsibilities compared to males. The other factor affecting the wage gap is the difference in number of time spent on self development. The analysis and results of our research prove our other hypothesis that more hours spending on self-development by employees negatively impact on pay inequality between males and females. Participants who have been spending more amount of time on improving their skills and competencies earn more. Our data analysis shows that since males use more time on the development of their personal skills they get higher earnings compared to women, consequently the income gap between them occurs.Furthermore, according to our findings, less females work in managerial positions, therefore the wage gap between men and women is observed. Men have more opportunities of working in management; therefore they get higher monthly income. The reason for this can be that in their career females experience more career interruptions than men. In contrast, the hypothesis of action of self-selection by employees is negatively related with the gender pay inequality between male and female employees, is rejected. It is argued that women mainly have unfavorable opinion about their skills, and therefore they are not so enthusiastic for achieving better jobs. However, according to our results men and women have almost the same level of self-selection. Similarly, while comparing the effects of taking career breaks on male and female employees, no relationship has been found and our hypothesis that the number of career breaks is positively related with the gender wage inequality is rejected. Furthermore, besides differences in individual characteristics of males and females, the unexplained part of the gap – discrimination is found as well. It is discovered that the percentage of discrimination level or unexplained part of the observed wage gap is more than explained part – independent variables’ impact. Therefore, it is concluded that besides differences in individual characteristics of male and female employees, discriminatory approach toward females also causes the pay inequality in the workplace.
Keywords: Business; Gender pay inequality.; Gender pay inequality -- Azerbaijan.; Gender pay inequality -- Banking -- Azerbaijan.